2014
DOI: 10.5194/nhess-14-525-2014
|View full text |Cite
|
Sign up to set email alerts
|

Application of GA–SVM method with parameter optimization for landslide development prediction

Abstract: Abstract. Prediction of the landslide development process is always a hot issue in landslide research. So far, many methods for landslide displacement series prediction have been proposed. The support vector machine (SVM) has been proved to be a novel algorithm with good performance. However, the performance strongly depends on the right selection of the parameters (C and γ ) of the SVM model. In this study, we present an application of genetic algorithm and support vector machine (GA-SVM) method with paramete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(31 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…These derived computational merits from LS-SVM can be confirmed in a number of studies found in the geodetic sciences domain (see e.g. Li & Kong, 2014;Mohammadi et al, 2015;Durmaz & Karslioglu, 2011;Ndehedehe, 2015, 2017 andreferences therein).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…These derived computational merits from LS-SVM can be confirmed in a number of studies found in the geodetic sciences domain (see e.g. Li & Kong, 2014;Mohammadi et al, 2015;Durmaz & Karslioglu, 2011;Ndehedehe, 2015, 2017 andreferences therein).…”
Section: Introductionsupporting
confidence: 59%
“…Artificial Neural Network (ANN) is one of the most attractive methods of computational intelligence to cope with non-linearity and time varying geodetic data due to its ability to learn and adapt to new dynamic environments. Numerous studies have shown successful implementation of ANN in the geodetic disciplines including but are not limited to deformation studies (Li & Kong, 2014;Huang, Wu, & Ziggah, 2016), meteorological studies (Mohammadi et al, 2015;Durmaz & Karslioglu, 2011), hydrological studies (Tiwari, J. Adamowski, & K. Adamowski, 2016;Deo & Şahin, 2016;Deo, Tiwari, Adamowski, & Quilty, 2017), tidal estimation (Okwuashi & Ndehedehe, 2017), change detection (Pal, 2009;Chang, Han, Yao, Chen, & Xu, 2010), geoid determination (Kavzoglu & Saka, 2005;Sorkhabi, 2015), and gravity field modelling (Turgut, 2016). Additionally, extensive studies on the suitability of ANN for coordinate transformation in both 2D and 3D have also been duly investigated by several authors (Tierra et al, 2008;Zaletnyik, 2004;Lin & Wang, 2006;Tierra, De Freitas, & Guevara, 2009;Tierra & Romero, 2014;Gullu, 2010;Gullu et al, 2011;Turgut, 2010;Mihalache, 2012;Yilmaz & Gullu, 2012;Konakoğlu, Cakir, & Gökalp, 2016;Ziggah, Youjian, Tierra, Konate, & Hui, 2016;Kumi-Boateng & Ziggah, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A search for optimal parameters in an SVM model plays a crucial role in building a landslide prediction model (Min and Lee 2005;Li and Kong 2014). To develop an efficient SVM model, C and r must be carefully predetermined.…”
Section: Previous Workmentioning
confidence: 99%
“…For rainfall-induced landslides, atmospheric rainfall is one of the most susceptible disaster-causing factors and directly affects the periodic displacement of a landslide (Lian et al, 2015;Ren et al, 2015). So the periodic term can be regarded as a function of time and rainfall.…”
Section: Landslide Periodic Displacement Modelingmentioning
confidence: 99%